2020
DOI: 10.1097/mou.0000000000000762
|View full text |Cite
|
Sign up to set email alerts
|

The role of leptin and obesity on male infertility

Abstract: Purpose of review Several studies suggest a strong association between leptin, obesity, and infertility with respect to the hypothalamic–pituitary–gonadal (HPG) axis, androgen regulation, and sperm production, but the direct mechanistic association between these is still largely unexplored. This review focuses on understanding the association between leptin, obesity, and male infertility. Recent findings Obesity is linked to fertility dysfunction in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 58 publications
0
19
0
7
Order By: Relevance
“…30 It is likely that the high leptin levels in obese patients play a role independent of the other factors involved in obesity on comorbid hypoandrogenism. 31 In contrast, another study suggested that low T could impact leptin levels. 32 In this study, castrated rats presented with the highest levels of leptin when compared with controls and those receiving exogenous T. 33 Since the majority of men in this study had normal serum T, low T was not a predictor of elevated leptin levels (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…30 It is likely that the high leptin levels in obese patients play a role independent of the other factors involved in obesity on comorbid hypoandrogenism. 31 In contrast, another study suggested that low T could impact leptin levels. 32 In this study, castrated rats presented with the highest levels of leptin when compared with controls and those receiving exogenous T. 33 Since the majority of men in this study had normal serum T, low T was not a predictor of elevated leptin levels (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore suggested that excessive leptin production may constitute a significant factor in the development of androgen deficiency and deterioration of male reproductive function. Nevertheless, the mechanisms binding leptin to the HPG axis and obesity are still not fully understood and the research results on the role of leptin in infertility development remains unclear [65][66][67]. In addition, in obese individuals, disorders on the hypothalamic-pituitary-gonads (HPG) axis have been observed.…”
Section: Figurementioning
confidence: 99%
“…Analogous to the context of hypoleptinaemia, the development of hyperleptinaemia also results in suppression of the HPG axis with resultant CH. However, unlike hypoleptinaemia, the mechanisms that mediate the effects of hyperleptinaemia on suppression of the HPG axis remain incompletely understood [ 83 ]. Obesity, particularly in the context of type 2 diabetes (T2D), is related to the development of resistance to the effects of leptin.…”
Section: Leptin As a Gatekeeper Between Survival And Reproductionmentioning
confidence: 99%